CHALLENGING THE EXISTENCE OF LEGAL TRANSLATION: A COMPREHENSIVE TRANSLATION THEORY - MANNONI, Michele (Comparative Legilinguistics, 2016)
This paper focuses on the lack of recognition of comprehensive and text-genre unrelated translation theories, a condition that keeps translators imprisoned in the old and sterile debate on free Vs. literal translation. By challenging two of the most common opinions, that is, the presumed existence of legal texts and legal-translation theories and that of the presumed utility of the notion of free and literal translation, this paper underlines the importance of the adoption of a comprehensive theory absolutely independent from the classification of the texts to be translated. More specifically, Popovič’s semiotics approach to translation gives great space to personal interpretation and anisomorphism, hence discarding once and for all the concept of faithfulness and equivalence in translation. As I attempt to prove in this paper, faithful and objective translations cannot exist, as translation is proved to be a subjective act: it is a creative process for which the interpreter is called to give his own interpretation on the signs created within the text.